Global, regional, and national burden and trends of pancreatic cancer, 1990–2021: a systematic analysis for the Global Burden of Disease Study 2021 - Liu, Chunlong; Liu, Pengpeng; Liu, Xue; Niu, Wang; Wu, Panpan; Yu, Jiangtao (Frontiers in Oncology, 2025)
BackgroundTo evaluate temporal trends, associated risk factors, and cross-national inequalities in the distribution of pancreatic cancer from 1990 to 2021.MethodsTemporal trends were measured using the average annual percent change and annual percent change. A comparative risk assessment framework was employed to estimate the proportion of disability-adjusted life years (DALYs) attributable to specific risk factors for pancreatic cancer. In addition, the unequal distribution of the global burden of pancreatic cancer was quantified using the inequality slope index and the concentration index, as recommended by the World Health Organization.ResultsFrom 1990 to 2021, the global incidence, prevalence, mortality and DALYs associated with pancreatic cancer have increased in absolute numbers. At the regional level, Central Asia recorded the highest values for all four indicators, while Western Sub-Saharan Africa experienced the most pronounced escalation in disease burden. Notably, the burden of pancreatic cancer was consistently higher in males than in females throughout the study period. Cross-national inequalities analysis reveals that disparities in pancreatic cancer burden are concentrated in countries with relatively higher socio-demographic index. To date, the high fasting plasma glucose remained the major risk factor that influenced the DALYs of pancreatic cancer, followed by smoking and high body mass index.ConclusionThe global burden of pancreatic cancer is rising, particularly among males and in high-income regions. This trend highlights the urgent need for targeted prevention strategies and improved management of modifiable risk factors, with a specific focus on these high-risk populations.